Radiating plasma species density distribution in EUV-induced plasma in argon: a spatiotemporal experimental study. (17th November 2015) - van der Horst, R M; Beckers, J; Osorio, E A; van de Ven, T H M; Banine, V Y
Abstract: In this contribution we experimentally study temporally and spatially resolved radiating plasma species density distribution in plasma induced by irradiating a low pressure argon gas with high energy photons with a wavelength of 13.5 nm, i.e. extreme ultraviolet (EUV). This is done by recording the optical emission spatially and temporally resolved by an iCCD camera as a function of the argon gas pressure. Our experimental results show that the emission intensity, i.e. density of radiating plasma species, depends quadratically on the gas pressure. The linear term is due to photoionization and simultaneous excitation by EUV photons, the quadratic term due to electron impact excitation by electrons generated by photoionization. The decay of radiating plasma species can be divided into two phases. At time scales shorter than 10 μ s (first phase), the decay is governed by radiative decay of radiating plasma species. At longer time scales (second phase, >10 μ s), the decay is dominated by diffusion and subsequent de-excitation at the wall. The experimental decay and expansion during this phase corresponds well with a simplified diffusion model. In order to gain more insight in this exotic type of plasma, we compare the electron density from previous measurements with the results obtained here.